Correction to: Treatment of effluents from Food Services Establishment (FSEs) by Physico-chemical processes: a case study for Trinidad & Tobago (Journal of Biological Engineering, (2024), 18, 1, (2), 10.1186/s13036-023-00344-w) - Shamika C.; Goutam B.; Vincent C. (My University, 2025)
Minor corrections were deemed necessary to rectify typographical errors that had occurred in the original article [1]. The changes do not affect the scientific content of the article, which has now been corrected. © The Author(s) 2024.